Effects of inhaled cannabis high in Δ9-THC or CBD on the aging brain: A translational MRI and behavioral study - Sadaka, Aymen H.; Canuel, Justin; Febo, Marcelo; Johnson, Clare T.; Bradshaw, Heather B.; Ortiz, Richard; Ciumo, Federica; Kulkarni, Praveen; Gitcho, Michael A.; Ferris, Craig F. (Frontiers in Aging Neuroscience, 2023)
With the recent legalization of inhaled cannabis for medicinal and recreational use, the elderly represents one of the newest, rapidly growing cohorts of cannabis users. To understand the neurobiological effects of cannabis on the aging brain, 19-20 months old mice were divided into three groups exposed to vaporized cannabis containing ~10% Δ9-THC, ~10% CBD, or placebo for 30 minutes each day. Voxel based morphometry, diffusion weighted imaging, and resting state functional connectivity data were gathered after 28 days of exposure and following a two-week washout period. Tail-flick, open field, and novel object preference tests were conducted to explore analgesic, anxiolytic, and cognitive effects of cannabis, respectively. Vaporized cannabis high in Δ9-THC and CBD achieved blood levels reported in human users. Mice showed antinociceptive effects to chronic Δ9-THC without tolerance while the anxiolytic and cognitive effects of Δ9-THC waned with treatment. CBD had no effect on any of the behavioral measures. Voxel based morphometry showed a decrease in midbrain dopaminergic volume to chronic Δ9-THC followed but an increase after a two-week washout. Fractional anisotropy values were reduced in the same area by chronic Δ9-THC, suggesting a reduction in gray matter volume. Cannabis high in CBD but not THC increased network strength and efficiency, an effect that persisted after washout. These data would indicate chronic use of inhaled cannabis high in Δ9-THC can be an effective analgesic but not for treatment of anxiety or cognitive decline. The dopaminergic midbrain system was sensitive to chronic Δ9-THC but not CBD showing robust plasticity in volume and water diffusivity prior to and following drug cessation an effect possibly related to the abuse liability of Δ9-THC . Chronic inhaled CBD resulted in enhanced global network connectivity that persisted after drug cessation. The behavioral consequences of this sustained change in brain connectivity remain to be determined.